PENGARUH PELATIHAN DAN PENGGUNAAN E-COMMERCE TERHADAP EKSPANSI USAHA DAN PENDAPATAN PENGRAJIN PERHIASAN DI KABUPATEN GIANYAR - Lestari, Ni Made Dwi Ary (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 8, No.8, Agustus 2019, pp (1697-1946), 2019)
Small industries in Gianyar Regency chew the  potential  to  be  developed  considering the local natural  resources  and z creativit of the community in  the field of art  or  craft  is enough  to contribute  to  improving the  welfare of  the  community and can support regional development programs. The handicraft industry, especially jewelry production, is the most common type among other industries found in Gianyar Regency. The existence of jewelery in Gianyar Regency has had a high socio-economic impact, improved people's lives and had an impact on the surrounding villages. The population used   in   this   study   was 238 jewelers in Gianyar Regency. The method of determining the sample in this study used the proportionate stratified random sampling method. The analysis technique   used   in   this   study is path analysis. The results of the study showed that training had a positive and significant effect on the business expansion of jewelry craftsmen, while the business expansion of jewelery craftsmen using e-commerce was no higher than those who did not use e-commerce in Gianyar Regency. Training, e-commerce and business expansion have a positive and significant effect on the income of jewelry craftsmen in   Gianyar   Regency. The  income of jewelery craftsmen using e-commerce is higher than those who do not use e-commerce in Gianyar Regency. There is an indirect influence of training and e-commerce on the income of jewelry craftsmen through business expansion in Gianyar Regency.  Keywords: Training, E-commerce, Business Expansion, and Income.